Mechanics of particles system in the Theory of Relativity - عسَّاف علي (Latakia University Journal -Basic Sciences Series, 2021)
Studying the mechanics of particle systems in special relativity is one of the most complex issues. However, this study sets us up to lay the groundwork for building a set of important laws. The motion of particle masses as a whole was determined by their energy, impulse and static mass. It was also found that the total energy of the system of mutual action requires taking into account the energies of these mutual acts between the particles. Contrary to the systems of the mutual acts of collisions, approximate formulas for interplay between charged particles were determined by studying the collision of relativistic particles-Compton’s effect. Finally, the case of the movement of the charged particles of weak interacts was discussed, and the movement of the interconnected particles was discussed through mutual electromagnetic acts using the concept of mutual action between the particles of the system.